Implementation of Learning Management Training Program at PT LPK Jamiatul Indonesia Edutech Certification in Improving Work Quality - Billy Eka Wardana (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2023)
The job training program organized by LPK JIEC is a program that aims to improve the competence of the workforce in Blitar in particular and throughout Indonesia. LPK JIEC is committed that the participants in this job training program can start their own business which includes planning, implementing, coaching, and evaluating learning. The purpose of this study was to determine the implementation of the job training program and the factors that hindered the successful implementation of the job training program at JIEC LPK. The method in this study uses a qualitative descriptive method. Data collection techniques used are interviews, observation, and documentation. The data validity technique uses source, method, and theory triangulation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The theoretical concept used in this study is Edward III's theory, namely 1) communication, 2) resources, 3) disposition, and 4) bureaucratic structure. The results of this study indicate that the implementation of job training programs in Blitar district is not optimal, especially in terms of communication and resources. In its implementation there are still obstacles such as 1) a shortage of instructors, 2) the absence of a Vocational Training Center, and 3) budget constraints in implementing job training programs. Evaluation of learning outcomes is carried out periodically, participants are satisfied with the training activities provided by PT. LPK JIEC to gain knowledge and skills.